Carbon mineralization dynamics of tropical peats in relation to peat characteristics - AKHMAD R. SAIDY; ZURAIDA T. MARIANA; FENGKY A. ADJI; ROSSIE W. NUSANTARA; IRMA FITRIA; SYAHRINUDIN SYAHRINUDIN (Biodiversitas Journal of Biological Diversity, 2018)
Saidy AR, Mariana ZT, Adji FA, Nusantara RW, Fitria I, Syahrinudin. 2018. Carbon mineralization dynamics of tropical peats in relation to peat characteristics. Biodiversitas 19: 1413-1421. Understanding the dynamics of carbon mineralization of peats in the tropical areas is of essential significance in controlling carbon dioxide (CO2) gas emission rates. An incubation study of tropical peats sampled from 3 different sites of the Barito Basin on the Borneo Island, Indonesia (uncultivated, used for paddy cultivation for £ 5 years and 5-10 years) was carried out to investigate a relationship between CO2 production and peat characteristics. Results of study revealed that land use change from uncultivated peats to paddy fields resulted in significant changes in the chemical structure of peat organic carbon. Carbohydrate contents of the peat decreased significantly as a consequence of the conversion of natural peats to paddy fields. However, the paddy peats contained higher lignin than uncultivated peats. Changes in the chemical structure of the tropical peats resulted in changes in carbon mineralization. Carbon mineralization of uncultivated peats ranged from 2925-5310 mg CO2-C kg-1 peat, while carbon mineralization of 1065-2678 mg CO2-C kg-1 C peat was observed for paddy peats. Moreover, carbon mineralization data obtained from the experiment fitted properly to a two-pool C mineralization model. The developed carbon mineralization model showed that slowly and rapidly decomposable pools have a close relation with rubbed fiber and carbohydrate content data. Thus, results of this study suggested that carbon mineralization of peats could be estimated appropriately using rubbed fiber and carbohydrate content data.